The Impact of Shopee's Youtube Ads Shopee Version 4.4 Mega Elektronik Sale on Purchase Intention - Zuhdan Ady Fataron (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2021)
Shopee's e-commerce in recent years has dominated the Indonesian online market because it offers a variety of attractive features. The support for Youtube Ads makes it easier for businesses to offer their products online. Shopee ads are packaged in Youtube Ads with a tagline that can spark consumer interest. One of the Shopee Ad taglines is Shopee 4.4 Mega Elektronik Sale. This tagline is quite booming considering that electronics is a part of modernization which is the basic need of generation Z. This study aims to measure how far the exposure of Shopee's 4.4 version of Shopee's advertisement is. Mega Elektronik Sale: New Refrigerator, Price Slams 50% on student buying interest. The novelty in this study refers to Youtube's capacity as an advertising medium to influence student purchase intentions as the largest market share of electronic products. The research is structured with a quantitative approach with a survey method. The results showed that 44% of students' buying interest was influenced by the Shopee advertisement version of the Shopee 4.4 Mega Elektronik Sale. The Shopee ad version of Shopee 4.4 Mega Elektronik Sale has a positive and significant effect on buying interest with a fairly strong correlation value, namely 0.663 which indicates that the stronger the advertising intensity can directly increase student buying interest.